STUDI LITERATUR: PERMASALAHAN DAN SOLUSI IMPLEMENTASI RAPOR PENDIDIKAN - Fytra; Sri Marmoah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education reports play an important role as a tool for mapping school quality, but their implementation often faces problems such as limited IT equipment, low teacher ability to access and understand the platform, difficulty in determining the main causes and alternative activities, potential program ineffectiveness due to a lack of contextual analysis, delayed technology integration among senior teachers, and low student engagement due to minimal family support. The solutions offered include the procurement of IT equipment, assistance for teachers in utilizing education reports, problem analysis training, program adjustments according to the school context, improving teacher performance through practical training and peer teaching, strengthening student involvement through project-based learning and home visits, active committee participation, and support from the education office through continuous training. With this collaboration, education reports can function optimally as a transformative tool to improve the quality of education.